Zinc finger proteins facilitate adaptation of a global insect pest to climate change - Tianpu Li; Jiao Guo; Guilei Hu; Fang Cao; Haiyin Su; Mengdi Shen; Huimin Wang; Minsheng You; Yuanyuan Liu; Geoff M. Gurr; Shijun You (BMC Biology)
Abstract Background Global climate change significantly impacts ecosystems, particularly through temperature fluctuations that affect insect physiology and behavior. As poikilotherms, insect pests such as the globally devastating diamondback moth (DBM), Plutella xylostella, are especially vulnerable to rising temperatures and extreme heat events, necessitating effective adaptive mechanisms. Results Here we demonstrate the roles of zinc finger proteins (ZFPs) in mediating thermal adaptability in DBM. We utilized a comprehensive approach involving cloning and bioinformatics analysis of three ZFPs, PxZNF568, PxZNF93, and PxZNF266, measurement of their expression levels in hot-evolved and control strains, and assessment of catalase enzymatic activity and total antioxidant capacity. We also employed CRISPR/Cas9 technology to create five stable homozygous knockout strains to elucidate ZFP functions in high-temperature tolerance. Survival rates under high-temperature stress and the critical thermal maxima (CTMax) of the knockout strains were significantly lower than the wild-type strain, and exhibited marked decreases in antioxidant capacity. Conclusion Findings reveal the importance of ZFPs in thermal adaptability of DBM, contributing critical insights for future pest management strategies in the context of a warming climate and laying the foundation for further exploration of ZFP functionality in agricultural pest control.